Implementasi Algoritma MD5 Pada Sistem MBKM Dan Di Universitas Bina Insan - Anggardha, Alvin; Rizki, Fido; Karman, Joni (Journal Global Technology Computer, 2024)
The problem in this study is that in the implementation of the MBKM program there are still many weaknesses and shortcomings, including the fact that currently Bina Insan University does not have its own system that can be used as an information media in providing the best service to students, the current system needed is a system with the application of the Md5 algorithm, the MD5 algorithm is one of the algorithms used to find out that the message sent has not changed while on the network, this system provides registration for each existing independent campus program so that all data will be centralized in one system, on the other hand, the MBKM section also requires a system that can convert credits to programs that have been followed, where in the program each student is given the right to get a conversion of 20 credits or the equivalent of one semester. The results of this study are that with this application, it can facilitate the MBKM in processing and converting the MBKM program, as well as speeding up and streamlining the registration process and converting MBKM program values ​​and providing information to students and lecturers about MBKM.